Targeting TXNIP in endothelial progenitors mitigates IL-8-induced neutrophil recruitment under metabolic stress - Julia Jolibois; Alison Domingues; Divina El Hamaoui; Raphaël Awaida; Mathilde Berger-de-Gaillardo; Daniel Guérin; David M Smadja; Perrine Marquet-DeRougé; Isabelle Margaill; Elisa Rossi; Valérie Nivet-Antoine (Stem Cell Research & Therapy, 2024)
Abstract Background This study explores the potential role of Thioredoxin-interacting protein (TXNIP) silencing in endothelial colony-forming cells (ECFCs) within the scope of age-related comorbidities and impaired vascular repair. We aim to elucidate the effects of TXNIP silencing on vasculogenic properties, paracrine secretion, and neutrophil recruitment under conditions of metabolic stress. Methods ECFCs, isolated from human blood cord, were transfected with TXNIP siRNA and exposed to a high glucose and β-hydroxybutyrate (BHB) medium to simulate metabolic stress. We evaluated the effects of TXNIP silencing on ECFCs’ functional and secretory responses under these conditions. Assessments included analyses of gene and protein expression profiles, vasculogenic properties, cytokine secretion and neutrophil recruitment both in vitro and in vivo. The in vivo effects were examined using a murine model of hindlimb ischemia to observe the physiological relevance of TXNIP modulation under metabolic disorders. Results TXNIP silencing did not mitigate the adverse effects on cell recruitment, vasculogenic properties, or senescence induced by metabolic stress in ECFCs. However, it significantly reduced IL-8 secretion and consequent neutrophil recruitment under these conditions. In a mouse model of hindlimb ischemia, endothelial deletion of TXNIP reduced MIP-2 secretion and prevented increased neutrophil recruitment induced by age-related comorbidities. Conclusions Our findings suggest that targeting TXNIP in ECFCs may alleviate ischemic complications exacerbated by metabolic stress, offering potential clinical benefits for patients suffering from age-related comorbidities.